Pengembangan Multimedia Interaktif dalam Pembelajaran Simulasi dan Komunikasi Digital - Handy Ferdiansyah; Abdul Haling; Nurhikmah H (Indonesian Journal of Learning Education and Counseling, 2021)
This research aims, (1) to know the description of the need for interactive multimedia development, (2) the validity, (3) practicality, and (4) the effectiveness of interactive multimedia products in learning simulation and digital communication. This research is a research and development (R&D) using the ADDIE development model with the subject of research as a material expert, a media expert, subject teacher, and forty students. Data was collected by interviews, questionnaires, and tests. The data obtained in this study are qualitative and quantitative data. The results of research are: (1) The level of need for interactive multimedia in learning learning simulation and digital communication for 10th grade student at SMK Muhammadiyah Sidenreng Rappang is very high. This is evidenced by the value of student learning outcomes that have reached the minimum completeness criteria after using interactive multimedia. (2) The results of the product validation data analysis are in the very valid category, this is obtained from the validation assessment of material and media experts. (3) The results of the respondents' evaluation of small group trials and teacher responses to interactive multimedia products are stated to be very practical. (3) Interactive multimedia in simulation learning and digital communication developed effectively as seen from the average recapitulation of learning outcomes assessment shows an increase in learning scores of all students is above the minimal completeness criteria value.